Non-Invasive Matrices for the Human Biomonitoring of PFAS: An Updated Review of the Scientific Literature - Martí Nadal; José L. Domingo (Toxics, 2025)
Per- and polyfluoroalkyl substances (PFAS) are synthetic chemicals widely used in consumer and industrial products due to their unique physicochemical properties. However, their persistence and bioaccumulative potential pose significant environmental and human health risks. This review focuses on the use of non-invasive matrices—urine, hair, and nails—for the human biomonitoring of PFAS, highlighting key findings from scientific studies. While urine offers a non-invasive and practical option, its limited sensitivity for long-chain PFAS requires further analytical advances. Hair and nails have demonstrated potential for use in biomonitoring, with higher detection frequencies and concentrations for certain PFAS compared to urine. The variability in PFAS levels across studies reflects differences in population characteristics, exposure sources, and geographic regions. This review emphasizes the need for standardized analytical methods, expanded population studies, and the use of complementary matrices to enhance the accuracy and reliability of PFAS exposure assessment.